Clinical Application of Ultrasound in Intensive Care Unit-Acquired Weakness - Patel, Sunil; Bear, Danielle; Patel, Brijesh; Puthucheary, Zudin (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Intensive care unit-acquired weakness (ICUAW) is common and prolongs the duration of mechanical ventilation and ICU length of stay and is also a leading cause of physical restriction up to five years later. Developing diagnostic tools that allow early identification and risk stratification in all critically ill patients is vital. Ultrasound is a cheap, reproducible and noninvasive imaging modality that can be used to assess multiple muscle groups. It has advantages over other imaging techniques that entail risks of radiation as well as the logistical concerns of moving critically ill patients. Ultrasound muscle indices can be monitored over time and may serve as predictors for ventilatory weaning and long-term outcomes. The diaphragm is frequently perturbed during critical illness, specifically when mechanical ventilation is initiated. Diaphragm thickness and excursion have been shown to support extubation strategy with the former serving as a marker of inspiratory effort in the absence of more specialist tests. The techniques are reproducible with appropriate training and practice and have been applied in clinical trials. Peripheral skeletal muscle ultrasound has been the subject of intense research in ICU-acquired muscle weakness. The technique has also been found to be reproducible and can serve as a surrogate marker to current volitional and non-volitional tests in the assessment of muscle ICUAW. This article outlines the application of musculoskeletal ultrasound and its role in the early recognition of ICUAW in three distinct muscle groups: (1) diaphragm (2) rectus femoris and introduces the potential of (3) parasternal muscles.Die Intensive-Care-Unit-Acquired Weakness (ICUAW), eine durch den Aufenthalt auf der Intensivstation erworbene Muskelschwäche, tritt häufig auf und verlängert die Dauer der künstlichen Beatmung und die Intensivliegezeit. Auch bis zu 5 Jahre danach ist sie eine der Hauptursachen für körperliche Einschränkungen. Die Entwicklung von diagnostischen Methoden, die eine frühzeitige Identifizierung und Risikostratifizierung bei allen kritisch kranken Patienten ermöglichen, ist von entscheidender Bedeutung. Die Sonografie ist ein kostengünstiges, reproduzierbares und nichtinvasives bildgebendes Verfahren, mit dem mehrere Muskelgruppen beurteilt werden können. Es hat Vorteile gegenüber anderen Bildgebungsverfahren, bei denen ein Strahlenrisiko besteht und es logistische Bedenken hinsichtlich der Verlegung kritisch kranker Patienten gibt. Die muskulären Marker im Ultraschall können im Zeitverlauf überwacht werden und als Prädiktor für das Weaning und den Langzeit-Outcome dienen. Das Zwerchfell ist bei kritischen Erkrankungen häufig beeinträchtigt, insbesondere wenn eine maschinelle Beatmung eingeleitet wird. Es zeigte sich, dass die Dicke des Zwerchfells und dessen Auslenkung nachweislich die Extubationsstrategie unterstützen, wobei die Dicke als Indikator für die Inspirationsbemühung dient, da spezialisierte Verfahren fehlen. Die Methoden sind mit entsprechender Ausbildung und Praxis reproduzierbar und wurden in klinischen Studien angewendet. Der Ultraschall der peripheren Skelettmuskulatur bei ICUAW war Gegenstand intensiver Forschung. Die Technik war reproduzierbar und kann als Ersatzmarker für die gängigen willentlichen und nichtwillentlichen Tests zur Beurteilung der ICUAW dienen. Die vorliegende Arbeit gibt einen Überblick über Einsatz und Stellenwert des muskuloskelettalen Ultraschalls in der Früherkennung der ICUAW in Bezug auf 3 verschiedene Muskelgruppen: (1) Zwerchfell, (2) M. rectus femoris und (3) parasternale Muskeln.